The Effect of Financial and Digital Literacy on Financial Behavior: Gender as a Moderating Variable Among Millenials and Generation Z - Latifah Dian Iriani; Nurul Hidayah; Muhammad Amin (Jurnal Manajerial, 2026)
Background – The penetration of technology into economy sector effects individual ability to adapt the use of technology. It has impacted on the changes financial behavior by the ease of shopping and payment transactions which leads to extravagant. Moreover, those generation has high rate of debt compared than other generation whilst they have high financial literacy and digital financial literacy. Both skills suggest do not automatically effecting good financial behavior. Previous research has focused more on the direct affecting of financial literacy and digital financial literacy on financial behavior. However, this study attempts to explore by using demographic vaariables such as gender, given that is a factor that can effecting financial decision making, especially for Milenial and Z generation. Aim – This study aims to investigate the effect of financial literacy and digital financial literacy towards financial behavior for Z and Milenial generation by using gender as moderating variable. Design / methodology / approach – This study uses cross-sectional survey conducting in Province of Papua Barat Daya. The sample consist of 420 individual of Milenial and Z generations. Structural Equation Model and Partial Least Square (SEM-PLS) used for analysis techniques. Findings – The result shows that gender does not significantly strengthen the effect of financial literacy and digital financial literacy on the financial behavior of milenial and Z generation. While financial literacy and digital financial literacy have significant effect toward financial behavior. Research implication – This study reinforces previous research that showing financial literacy and digital financial literacy contribute in shaping financial behavior, particularly among young generation. Furhermore, the moderating variable of gender do not significantly strengthen the influence of financial literacy on digital financial literacy due to the widespread exposure and equitable to information. Policy maker, teacher, and financial institution should collaborate to design in order to strengthen young generation understanding of financial literacy and digital financial literacy through comprehensive learning embedded in the curriculum    Limitations – The future research can use the alternative moderating variable that used in order to further analysis towards financial literacy and digital financial literacy to financial behavior.